2002
DOI: 10.1021/la025711k
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis and Electrochemical Characterization of a Thin Phase of CuxS (x → 2) on ITO Electrode

Abstract: Cu x S (x → 2) thin films were obtained by sulfidization of copper thin films previously obtained by spin-coating from a dichloromethane solution of [Cu(II)(2-ethyl hexanoate)2(H2O)2] deposited on ITO substrate, irradiated with UV light and electrochemically reduced. Through cyclic voltammetry experiences performed in a 0.05 M Na2B4O7 buffer solution containing 5 mM Na2S, the electroformation mechanism of Cu x S phase is controlled by a first electron transfer, obtaining an initial formation of Cu(HS)ads that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…So far, a variety of methods were employed to the deposition of CuS thin films, such as chemical vapor deposition [25], thermal coevaporation [2], successive ionic layer adsorption and reaction (SI-LAR) [9], photochemical deposition [26], electrochemical method [27] and chemistry bath deposition (CBD) [28][29][30]. Among these, the chemical bath deposition is an attractive technique for the deposition of semiconductors as it does not require sophisticated instrumentation like vacuum system and other expensive equipments.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a variety of methods were employed to the deposition of CuS thin films, such as chemical vapor deposition [25], thermal coevaporation [2], successive ionic layer adsorption and reaction (SI-LAR) [9], photochemical deposition [26], electrochemical method [27] and chemistry bath deposition (CBD) [28][29][30]. Among these, the chemical bath deposition is an attractive technique for the deposition of semiconductors as it does not require sophisticated instrumentation like vacuum system and other expensive equipments.…”
Section: Introductionmentioning
confidence: 99%
“…Further more, Single HgS (cinnabar) crystal is a famous natural chiral crystal and expected to be used for stereochemical reactions [12]. Much effort has been devoted to the synthesis of metal chalcogenide of various morphologies, such as rods [13], wires [14], tubes [15], etc., with various techniques and methods involving microwave synthesis [16], sonasynthesis [17] and electrochemical deposition [18] and so on. The formation of spatial patterns of metal chalcogenide is of special interest because subtle influencing factors may result in completely different crystal shape.…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2Àx S as materi- 13 als, particularly in its thin film form, maintain transmittance in the 14 infrared, low reflectance (<10%) in the visible, and relatively high 15 reflectance (> 15%) in the near-infrared region, which are ideal 16 characteristics for solar energy adsorption [2]. Copper sulfide can 17 exist as seven solid phases with various stoichiometries, Cu 2Àx S, 18 (0 < x < 1), including Cu-rich Cu 2 S (chalcocide), Cu 1.97 S (djurleite), 19 Cu 1.8 S (digenite), Cu 1.75 S (anilite) Cu 1.12 S (yarrowite), Cu 1.06 S 20 (talnakhite) and CuS (covellite) [3,4]. Nair and coworkers [5] 21 reported that all of Cu 2Àx S compounds exhibited a p-type 22 semiconductor characteristic with copper vacancy defect as 23 acceptors, which is the most important reason for their applica- 24 tions in the photovoltaic devices.…”
mentioning
confidence: 99%
“…He and his coworkers synthesized uniform, 44 small sized CuS NCs prepared via a facile sol-gel method without 45 using template and complicated post-treatment [14]. Moreover, a 46 variety of methods were employed to deposit Cu 2Àx S thin films, 47 such as chemical vapor deposition, thermal co-evaporation [15], 48 photochemical deposition [16], electrochemical method [17] 49 and chemical bath deposition (CBD) [18][19][20][21]. Among these, 50 the chemical bath deposition is an attractive technique for 51 the deposition of semiconductors as it does not require sophisticated 52 instrumentation like vacuum systems or other expensive equip-53 ment.…”
mentioning
confidence: 99%